Efficacy and Safety of Central Memory T Cells Combined With Adjuvant Therapy to Prevent Recurrence of Hepatocellular Carcinoma With Microvascular Invasion: A Pilot Study - Cai, Jianqiang; Zhao, Jianjun; Liu, Defang; Xie, Huangfan; Qi, Hailong; Ma, Junfan; Sun, Zhongjie; Zhao, Hong (Frontiers in Oncology, 2021)
Background Postoperative adjuvant transcatheter arterial chemoembolization (TACE) following curative hepatectomy has been reported to improve the clinical outcomes of hepatocellular carcinoma (HCC) patients with microvascular invasion (MVI), but more endeavors are required to achieve greater clinical benefit. Central memory T cell (Tcm) self-transfusion has shown superior antitumor activity in several preclinical studies, however clinical studies are rare. The aim of this study was to evaluate the clinical benefit and safety of combination treatment with Tcm self-transfusion and TACE as adjuvant treatment in HCC patients with MVI after curative hepatectomy. Methods From October 2016 to September 2018, primary HCC patients with histologically confirmed MVI who underwent curative hepatectomy at the Cancer Hospital of the Chinese Academy of Medical Sciences were recruited for this study. The patients were divided into a Tcm group (combined Tcm self-transfusion with TACE treatment) or a control group (TACE treatment alone) according to their willingness. The recurrence-free survival (RFS), quality of life (QOL) score and adverse events of each patient were recorded within 2 years. Results A total of 52 patients were enrolled, and 48 were eligible for the final data analysis. The median follow-up time was 20.5 months (95% CI: 17.05-22.55 months). The median RFS time was 9.5 months in the control group; the cutoff date was not reached in the Tcm group (when the follow-up duration was 12 months, P=0.049, HR=0.40; 95% CI: 0.16-0.99). Compared to the control group, 1- and 2-year RFS rates were higher in the Tcm group (72.0% vs. 46.4% and 58.18% vs. 39.14%, respectively).¬ Multivariate analysis did not indicate that Tcm treatment was an independent prognostic factor associated with HCC recurrence (P=0.107, HR=2.312; 95% CI: 0.835-6.400), which might be due to the small sample size of this study. Nevertheless, Tcm treatment effectively improved a reduced QOL due to HCC and liver function injury. Finally, the safety profile of Tcm treatment in this study was good, without any serious adverse events. Conclusions This pilot study showed that Tcm self-transfusion combined with TACE treatment might be a beneficial adjuvant therapy with good safety for primary HCC patients with MVI after curative hepatectomy.